2020
DOI: 10.7759/cureus.8658
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Health-Related Quality of Life in Patients With Diabetic Foot Ulcer: A Cross-Sectional Study From Saudi Arabia

Abstract: Background and objective Diabetic foot ulcers (DFU) have been shown to have a high impact on the patients’ perceived health-related quality of life (HRQOL). The aim of this study was to estimate the HRQOL and its related risk factors in patients with foot ulcers associated with type 2 diabetes mellitus (T2DM). Methods This cross-sectional study was performed on 81 patients with DFU, from January 2019 to July 2019 at the Prince Sultan Military Medical City (PSMMC), Riyadh, Saudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 27 publications
2
15
1
3
Order By: Relevance
“…Another study also found that female gender, overweight, peripheral vascular disease, and stress in life may be related to lower QoL in DFU patients (10). A study from Saudi Arabia found that many factors may affect the QoL of DFU patients, including age, educational status, occupational status, income, and complications (11). In the present study, low psychological resilience, older age, lower perceived social support, and higher level of HbA1c were identified as risk factors of QoL.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study also found that female gender, overweight, peripheral vascular disease, and stress in life may be related to lower QoL in DFU patients (10). A study from Saudi Arabia found that many factors may affect the QoL of DFU patients, including age, educational status, occupational status, income, and complications (11). In the present study, low psychological resilience, older age, lower perceived social support, and higher level of HbA1c were identified as risk factors of QoL.…”
Section: Discussionmentioning
confidence: 96%
“…Alrub et al reported that female gender and obesity were related to poorer QoL in Jordanian DFU patients (10). Al Ayed et al reported that, in addition to gender and obesity, education, occupation, income, and the number of complications were predictors of poor QoL in DFU patients (11). A recent meta-analysis indicated that some other risk factors such as the level of C-reactive protein (CRP), ulcer size, and level of glycated hemoglobin (HbA1c) had significant impacts on the QoL of DFU patients (12).…”
Section: Introductionmentioning
confidence: 99%
“…A research by Tini in 2018 found that the majority in this study gender was women (80%). Gender can also affect the occurrence of obesity, in this study the majority of respondents were 67 people (65.7%) women 8. It can be seen that eighteen percent of the samples were in the age group of 40-45 years and 56-60 years old.…”
mentioning
confidence: 49%
“…A previous study by Mousab Al Ayed et al alluded this to longer periods of hospitalization and overall morbidity. 19…”
Section: Discussionmentioning
confidence: 99%